Histochemical changes induced by Trichoderma spp. And potassium phosphite in common bean (Phaseolus vulgaris) in response to the attack by Colletotrichum lindemuthianum - Figueira, Eliana Peliçon Pereira; Kuhn, Odair José; Martinazzo-Portz, Tatiane; Stangarlin, José Renato; Pereira, Marcos Donizete Peliçon [UNESP]; Lampugnani, Camila (Universidade Estadual de Londrina, 2020)
Induction of resistance in common bean (Phaseolus vulgaris) has been considered a promising alternative to control anthracnose. Among the changes generated in the induction of resistance, structural changes have been reported by several authors as an efficient form of resistance to the stress plants undergo. Histochemical analysis techniques have been used to investigate tissue changes triggered by induction of resistance. Thus, this study aims to investigate certain histochemical changes suffered by common bean plants induced with potassium phosphite and Trichoderma spp. in response to the attack by Colletotrichum lindemuthianum, aiming to determine the host response pattern in terms of structural changes, associating it to possible disease control. Treatments consisted of isolates T. harzianum (isolate TOD1) and T. virens (isolate TM4), leaf fertilizer potassium phosphite Fertilis®, and distilled water (control). Inducers were applied to common bean alone or associated, consisting of five treatments plus the control treatment. The six treatments were evaluated for the absence and presence of C. lindemuthianum in a factorial scheme (6×2). Treatments allowed evaluating the severity of anthracnose in common bean, location of H2O2, lignin deposition, and hypersensitivity response in common bean hypocotyl by histochemical staining. Potassium phosphite and combinations of T. virens and T. harzianum with potassium phosphite efficiently reduced disease severity under greenhouse conditions, reaching 68, 84, and 71%, respectively. Studies with hypocotyl showed that T. harzianum + potassium phosphite and T. virens + potassium phosphite accelerated the H2O2 accumulation process and lignin deposition at the pathogen penetration site, in addition to the hypersensitivity reaction through the resistance-inducing activity, contributing to the protection of common bean against anthracnose caused by C. lindemuthianum.
Keywords: Anthracnose; Hypersensitivity response; Induction of resistance; Oxygen-reactive species